2009
DOI: 10.1186/1743-8977-6-34
|View full text |Cite
|
Sign up to set email alerts
|

Soluble iron modulates iron oxide particle-induced inflammatory responses via prostaglandin E2 synthesis: In vitro and in vivo studies

Abstract: BackgroundAmbient particulate matter (PM)-associated metals have been shown to play an important role in cardiopulmonary health outcomes. To study the modulation of PM-induced inflammation by leached off metals, we investigated intracellular solubility of radio-labeled iron oxide (59Fe2O3) particles of 0.5 and 1.5 μm geometric mean diameter. Fe2O3 particles were examined for the induction of the release of interleukin 6 (IL-6) as pro-inflammatory and prostaglandin E2 (PGE2) as anti-inflammatory markers in cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…Such event could have severe consequences in case of interaction with DNA [32], as suggested by the activation of p53 and H2AX pathways in our experimental settings, and could therefore explain the genotoxic effects often associated with CNT exposure [33-37]. Interestingly, iron oxide particles have been shown to dissolve inside murine alveolar macrophages [38], suggesting a potential additional mechanism of toxicity related to the interaction of soluble iron with proteins. However, since the intracellular levels of the iron storage protein H-Ferritin were not increased in SWCNT-exposed macrophages, the generation of ionic iron from the detached iron nanoparticles seems unlikely, at least within the timeframe of exposure used here.…”
Section: Resultsmentioning
confidence: 96%
“…Such event could have severe consequences in case of interaction with DNA [32], as suggested by the activation of p53 and H2AX pathways in our experimental settings, and could therefore explain the genotoxic effects often associated with CNT exposure [33-37]. Interestingly, iron oxide particles have been shown to dissolve inside murine alveolar macrophages [38], suggesting a potential additional mechanism of toxicity related to the interaction of soluble iron with proteins. However, since the intracellular levels of the iron storage protein H-Ferritin were not increased in SWCNT-exposed macrophages, the generation of ionic iron from the detached iron nanoparticles seems unlikely, at least within the timeframe of exposure used here.…”
Section: Resultsmentioning
confidence: 96%
“…The cell homogenates were centrifuged at 10,000 x g for 15 min at 4°C. The supernatants were taken for measurements of protein and lipid mediators [25,26]. Analysis of the cell lysates is a reliable tool to quantify the parameters in each sample [25].…”
Section: Methodsmentioning
confidence: 99%
“…The observed oxidative stress and inflammation could be due to free iron released from the particles. Although iron oxides are relatively insoluble in aqueous conditions, Beck-Speier et al reported that Fe 2 O 3 particles can dissolve in the acidic lysosomal environment after phagocytosis by alveolar macrophages [27]. However, they also report that the intracellular free iron may suppress particle induced inflammation since the level of inflammatory marker IL-6 was not significantly elevated.…”
Section: Animal Inhalation Studies On Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…A characterization of welding fumes conducted by Jenkins determined the presence of magnetite (Fe 3 O 4 ) in the GMAW process and MnFe 2 O 4 in the SMAW process [25]. A more recent welding fume characterization study assessed the components of arc welding fume and found three crystalline phases of iron: Fe 0 , FeO and Fe 3 O 4 [27]. It is important to note that characterization of welding fumes has confirmed the presence of nanosized iron oxide particles, providing likely evidence for occupational exposure to inhaled particles of this size [25,28].…”
Section: Occupational Inhalation Exposure To Iron Oxide Particlesmentioning
confidence: 99%